1991
DOI: 10.1177/000348949110000610
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Vertical Transmission of Human Papillomavirus and Subsequent Development of Respiratory Tract Papillomatosis

Abstract: This study prospectively examined the potential for human papillomavirus (HPV) to be transmitted vertically to newborns during delivery. Exfoliated cervical cells were extracted from 72 pregnant women during the third trimester and again during labor prior to delivery, and tested for the presence of HPV DNA. These results were compared with HPV DNA specimens from their newborns, who were sampled by exfoliated cells from the oral-pharyngeal cavity and vulva or tissue from the foreskin 24 to 72 hours after deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 14 publications
2
43
0
1
Order By: Relevance
“…The HPV positivity rate in oral specimens collected from 68 current male partners who visited the clinic with the pregnant women was 5.9% (4). None of the infected men had female partners who concurrently were infected in either the oral or genital areas; thus there also was no viral concordance between partners.…”
Section: Oral-hpv Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The HPV positivity rate in oral specimens collected from 68 current male partners who visited the clinic with the pregnant women was 5.9% (4). None of the infected men had female partners who concurrently were infected in either the oral or genital areas; thus there also was no viral concordance between partners.…”
Section: Oral-hpv Resultsmentioning
confidence: 98%
“…HPV infection also may be transmitted vertically during parturition [4][5][6] . This proposition is of concern since the prevalence of detectable maternal HPV infection during pregnancy reportedly may rise during the second and third trimester above that of non-pregnant women, thus increasing the probability of HPV exposure to perinatal transmission at the time of delivery 5,7 .…”
mentioning
confidence: 99%
“…HPV is positive in the airways of neonates and in maternal genital condylomas, which suggests that it is transmitted in the birth canal, from mothers with genital condylomas. 27 Since the serologic diagnosis of HPV is inadequate, molecular diagnosis has been more popular in recent years. 28 Epidemiological studies revealed different results in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is positive in the airways of neonates and in maternal genital condylomas, which suggests that it is transmitted in the birth canal, from mothers with genital condylomas. 12 Occasionally, however, HPV is positive in newborns of mother with no history of genital condylomas, suggesting the possibility of latent or subclinical products, which may explain recurrences after a long time period of disease remission. 13 Some studies have found HPV in benign laryngeal lesions such as polyps, Reinke's edema, leukoplasia, lichen planus, and even in the normal mucosa of the mouth.…”
Section: Introductionmentioning
confidence: 99%